ETHNOLOGICAL FIELD STUDIES IN FORMOSA BY PAUL IBIS AND JOSEPH STEERE IN 1873-1875 (COMPARATIVE REVIEW) - Valentin Ts. Golovachev (Сравнительная политика)
Paul Ibis (1852-1877), the Russian Navy Navigation Corp’s ensign, undertook a lone “ethnographic trip” to Formosa (Taiwan) in January-February 1875. During the limited 1.5 month’ time, as Ibis proceeded from Takao to most Southern and, thereafter, to Northern end of the island, he collected, arranged and published many unique ethnological materials on aborigines and Chinese immigrants of Formosa. However, Paul Ibis was not the first researcher to carry out such a complex and daring scientific trip. The prominent American natural-science scholar Joseph Bill Steere (1842-1940) visited the island prior to Paul Ibis in October 1873 – March 1874. During the 6 months’ expedition he collected numerous species of local flora and fauna, as well as many ethnographic and linguistic materials for the University of Michigan. This article contains a comparative general review of field materials, research methods, process and results of the ethnological work conducted by two explorers, who visited Formosa and studied it almost synchronously and independently of each other. As a comparison of their papers reveals, Paul Ibis’ articles (2 pieces published in 1876-1877) are in no way inferior to the general academic level of J.B. Steere’s articles, and even surpass it in some aspects.